ICT APPLICATION IN HUMAN RESOURCE MANAGEMENT PRACTICES IN SMALL BUSINESSES: OPPORTUNITY AND CHALLENGES - Katerina Hadzi Naumova-Mihajlovska; Vladimir Petkovski (Institute of Economics-Skopje, 2023)
: In recent years, information technology has effects on almost every aspect of our society, as well as on organizational processes, including human resource management (HRM) processes and practices. Continued in novations in technology fundamentally increased the effectiveness of HRM and improve their work efficiency. Main purpose of the paper is on base of a literature review to analyze main challenges and opportunity behind the adop tion of ICT in HRM by small business. The research results presented in this paper are part of the project Main human resource management challenges for small businesses (Главни предизвици на малите бизниси во управувањето со човечките ресурси), NIP.UKIM.21-22.21, Ss. Cyril and Methodius University in Skopje, Republic of North Macedonia
Keywords: Information and Communication Technologies (ICT), Human Resource Management (HRM), small business